PENGARUH RELIGIUSITAS KELUARGA DAN JENIS SEKOLAH TERHADAP PERILAKU MORAL SISWA SMK DI KABUPATEN BANTUL - Ani Rusmiyati (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2019)
This study aims to determine the effect of the family religious habit and school types to the SMK (vocational school) students’ moral behaviors in Bantul regency. This study was using the quantitative descriptive method. The subjects of the study were SMK students in Bantul. The data collection technique used a research scale, interview, data presentation and data verification. The data analysis technique was multiple regressions analysis. The result of this study shows that there is significant positive effect of family religious habit concerning students’ moral behaviors. The higher the family religious habit, the better the students’ moral behaviors level. On the contrary, the lower the family religious habit, the lower the students’ moral behaviors level will be. There is a positive and significant effect of school types in relation to students’ moral behaviors. Furthermore there is significant difference between students who study in the religious schools and those who do not. Students of religious schools tend to have higher moral behavior level. There is a significant and simultaneous effect of family religious habit and school types in relation to students’ moral behavior. It indicates that religious environment at family and school may affect the students’ moral behaviour.